Plato, Carroll, Wittgenstein and Kripke on the Problem of Private Language - Pučiliauskaitė, Saulenė (Problemos, 2003)
The article is centered around the problem of "private language" as presented in Wittgenstein?s philosophy. The problem is related to the same problem introduced by Plato and by the work of Lewis Carroll. Therefore the article puts forward a hypotesis about the work of Carroll as an inspiration to late Wittgenstein’s work. The article also analyzes the approach of Saul Kripke to the proper understanding of Wittgens tein’s problem, and draws the conclusion about the impossibility of "private language". This conclusion is in agreement with the irony of Plato and the grotesque wit of Carroll. From the proof of the impossibility of "private language" it follows, that logically "private world" is also impossible.